Correlation Of Water Quality Factors and Stock Density to Glucose and Cortisol Levels in Cantang Grouper (Epinephelus fuscoguttatus X Epinephelus lanceolatus) Raised in Conventional Ponds - Saputra, Alfian Rahmadhani Satria Hani; Shohifah, Isnatul Umu; Sulmartiwi, Laksmi; Mahasri, Gunanti; Andriyono, Sapto (Jurnal Media Akuakultur Indonesia, 2023)
The purpose of this study was to find a correlation between density and water quality with glucose and cortisol levels in Cantang grouper (Epinephelus fuscoguttatus x Epinephelus lanceolatus) reared in ponds as an indicator of stress. This study uses a time series sampling method in its implementation. There were 10 Cantang grouper samples taken in this study per pond with sizes ranging from 20-30 cm. Fish samples were taken from 3 different ponds so that a total of 30 cantang grouper samples were found, while 1.5 L of water samples were taken from each pond. The results of measuring glucose levels showed that the highest average glucose levels in fish blood were obtained in pond number 6 (51.22 ± 14.9 mg dl-1) while the lowest was in pool number 5 (40.95 ± 15.2 mg dl-1). Similar to glucose levels, the results of blood cortisol measurements showed that the highest average cortisol levels in fish blood were obtained in pond number 6 (116.45 ± 5.49 ng ml-1) while the lowest was in pool number 5 (112.64 ± 4.55 ng ml-1). Based on the results of the regression analysis between the variables of water quality factors and stocking density on glucose levels (Figure 1), an R-value of 0.729 is obtained, which means that there is a 72.9% relationship between the variables of water quality factors and stocking density on glucose (moderate relationship). While the results of the regression analysis between the variables of water quality factors and stocking density on cortisol levels (Figure 2), an R-value of 0.722 was obtained, which means that there is a 72.2% relationship between the variables of water quality factors and stocking density on cortisol (moderate relationship). According to this research study, water quality factors that had a significant effect (p>0.05) on glucose levels in Cantang grouper were Temperature, DO, Salinity and Ammonia.